A qualitative investigation into customer participation on social customer relationship platforms adopted by home-based enterprises - Reddy, Shalen (Graduate School of Business (GSB), 2025)
The emergence of social media has made it possible for home-based businesses to manage client interactions online. Low user acceptance rates are responsible for up to two-thirds of failures, have historically plagued small and medium enterprises that have implemented a customer relationship management method (Heller Baird & Parasnis, 2011). This study investigates the factors that influence customer participation on social customer relationship management systems used by small and medium enterprises, with a particular emphasis on home-based businesses. It addresses the Question: How can customers be persuaded into participation on social customer relationship platforms of home-based enterprises? A constructivist grounded theory technique was used to conduct this study. Data was gathered from nine home-based businesses through social media recommendations based on active customer engagement. A four-cycle model is implemented to analyse the data that was obtained through coding. Seven key variables emerge, and a customer participation theory is developed. This study concludes that for home-based businesses to improve customer participation on social networks they must first build trust with their target market. This research contributes to literature of home-based enterprises operating in the social customer relationship management space with the development of a substantive theory to improve customer participation thereby increasing customer engagement. Future studies should aim to broaden their findings by including all SME consumers. In this way added dimension may be developed with the inclusion of platform developers and business owners